2005
DOI: 10.14221/ajte.2005v30n2.1
|View full text |Cite
|
Sign up to set email alerts
|

Cooperating Teachers as School Based Teacher Educators : Student Teachers' Expectations

Abstract: Abstract:The National Institute of Education (NIE)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
4
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 9 publications
3
4
0
Order By: Relevance
“…In similar research akin to our study, many topics of expectations were identified, for instance, Demirkol (2004), Atputhasamy (2005) and Nguyen and Hunter (2018) addressed four themes: which are mainly orientation, collegiality, counselling and leadership. Even though our questionnaire study results maintained the same themes, the rank order of priority is relatively different in which as Guidance precedes Leadership and Counseling occupies the final rank order, precisely after Colleagueship.…”
Section: Findings and Discussionsupporting
confidence: 60%
“…In similar research akin to our study, many topics of expectations were identified, for instance, Demirkol (2004), Atputhasamy (2005) and Nguyen and Hunter (2018) addressed four themes: which are mainly orientation, collegiality, counselling and leadership. Even though our questionnaire study results maintained the same themes, the rank order of priority is relatively different in which as Guidance precedes Leadership and Counseling occupies the final rank order, precisely after Colleagueship.…”
Section: Findings and Discussionsupporting
confidence: 60%
“…The Workforce Plans states that the average public school (both primary and secondary) teacher is 46 years old and has served in the department for 15 years. Similar data was generated in the Staff in Australian Schools survey conducted by the Australian Council for Educational Research and colleagues (see: McKenzie et al, 2011) and in the similar work conducted in the United States (RATE IV, 1990 cited in Atputhasamy, 2005). Any shift in the demographic profile of teachers, and by virtue potential co-operating teachers, especially one that reduces the gap of tenure between the pre-service and co-operating teacher will recast the temporal dimensions of the profession.…”
Section: A Temporal Professionsupporting
confidence: 60%
“…We see 'work-integrated learning' as including a breadth of activities, including but not exclusively, practicum placements, volunteering and outreach programs, fieldwork visits, shadowing/observations and other opportunities for higher education students to participate in profession-based activities. With an increasing demand for graduates who are 'work-place ready', particularly within an increasingly globalised community (Cooper, Orrell, & Bowden, 2010), it is hardly surprising that work-integrated learning has been applied to a substantial number of university professional degree programs, including nursing and other health professions, social work and education degrees (Atputhasamy, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Research studies suggest that student teachers view their practicum experiences as extremely important and essential for their induction into professional life (Zeichner & Gore, as cited in Keogh, Dole, & Hudson, n.d.). They believe that the practical experiences of supervisors who observe their lessons, receiving feedback and practicing various teaching strategies during the school experience are the most important factors in student teachers' professional growth (Tisher, as cited in Atputhasamy, 2005 performance often takes the form of a supervisor's comments immediately after the lesson is over. This must be followed by another attempt at the lesson and then evaluation for improvement.…”
Section: Teaching Practicummentioning
confidence: 99%